Identification of Gaps in the Implementation of Social Commerce in Startups - Negarsadat Mesbahi Jahromi ; Vahidreza Mirabi; Serajeddin  Mohebbi ; Mehdi Bagheri (مطالعات مدیریت کسب و کار هوشمند, 2019)
The share of social commerce in Iran is relatively small compared to the developed countries in the field of social commerce. So, it important to identify factors which are critical in the implementation of social commerce. The main purpose of this research is to identify legal and behavioral gaps on the implementation of social commerce among the startups. The statistical population in the qualitative section consists of social commerce experts in knowledge-based companies in the field of information technology in the science and technology park of Tehran University. Experts were identified using snowball and judgmental sampling techniques. According to the adequacy of data, 20 interviews were performed in total. The statistical population in the quantitative section consisted of the managers of startup companies located in Tehran. Two-step sampling method was used to determine the sample size. Data in qualitative section were collected through deep interviews and in the quantitative section it was collected through questionnaires. Data was analyzed using SmartPLS2 software in quantitative section. The results show that changes in business environment is as causal conditions. The pivotal phenomenon including: the implementation of social commerce, the contextual conditions including the business cultures and legal gaps, the interfering conditions including the behavioral gaps, and business resource conditions, and strategies including the reliability of online markets and the development of technical infrastructure have been identified. Ultimately, the consequences of this study have been enhancing business ease and improving sales performance.